Private Equity firms financing in the time of crisis - Šťastná, Helena (2025)
The purpose of this thesis is to study the impacts of sovereign wealth funds on financing of private equity in times of economic crisis. Even though private equity firms rely on leveraged buyouts, growing restraints due to tighter credit markets and macroeconomic instability makes them opt for different solution. Nevertheless, a number of them have sought out sovereign wealth funds as co-investors. This research seeks to understand how private equity deals backed by Sovereign wealth funds differ in with regard to their investment resilience, behaviour, sensitivity to macroeconomic factors, and overall durability when compared to traditional private equity transactions. Using correlation analysis and SARIMA time-series forecasting, the thesis examines the relationship between deal volume and key economic indicators such as interest rates, inflation, credit spreads, GDP, and stock market performance. Sovereign Wealth Fund-backed deals display counter-cyclical behaviour in comparison to traditional private equity deals, which increase the volatility and sensitivity towards credit market conditions, interest rate fluctuations. According to the SARIMA model, deal volume will stabilize in the coming years, which implies a shift in the economic climate towards long-term strategic low-risk investment valuation and recovery phase.